DISIPLIN HUKUM YANG MEWUJUDKAN KESETARAAN DAN KEADILAN GENDER (LAW DISCIPLINE TO MANIFEST GENDER EQUALITY AND JUSTICE) - Nafi, Tien Handayani (UI Scholars Hub, 2012)
This 248-page book enable the readers to see the author’s intent to desribe the position of law and gender in law discipline, hence the public (especially the law students) can understand that law and gender can be manifested through law disciplines.